Atmospheric stability of arsines and the determination of their oxidative - Jakob, Ronit; Roth, Anja; Haas, Karsten; Krupp, Eva M.; Raab, Andrea; Smichowski, Patricia Nora; Gomez, Dario Gustavo; Feldmann, Jörg (Royal Society of Chemistry, 2010)
Fil: Jakob, Ronit. University of Aberdeen; Reino Unido